APUCEN INTERNATIONAL YOUTH VOLUNTEER AWARDS 2017 - MPRC, Pusat Media & Perhubungan Awam (2017)
PENANG, 11 March 2017 The 3rd International AsiaPacific UniversityCommunity Engagement Network (APUCEN) Summit is inviting entries from its 87 members from 19 countries, for its inaugural APUCEN International Youth Volunteer Awards 2017.